Biomechanical analysis of differences in badminton smash and jump smash between Taiwan elite and collegiate players - Tsai, C. L.; Huang, C.; Chang, S. S. (1998)
Introduction: Badminton is one of the most popular sports in Taiwan. Previous studies focused on the description of one group of Badminton players. The purpose of this study is to compare the smash and jump smash techniques performed by Taiwanese elite and collegiate players. We are interested in analyzing the two types of Badminton strokes from the phase of preparation position to the point of making contact with the shuttlecock. Methods: Two Peak-Performance high speed video cameras operating at 120Hz, were simultaneously used to obtain 3-D data from 7 Taiwan elite players and 4 collegiate players. A t-test was used to test the selected variables at the 0.05 significance level between the two groups of players. The selected variables included the shuttle velocities, flying angle, contact height, position of center of mass (CM) at the lowest and at the contact, angles and angular velocities of the upper limb and relative distance between CM and contact point. Results: Table 1 shows the significant differences between the two groups of players in the smash and the jump smash. In the smash stroke, the shuttle velocities of the elite players were from 55m/s to 70 m/s, those of the collegiate players were from 50- 58 m/s. The elite players are significantly faster than the collegiate players. In the jump smash, the shuttle speed and the downward flying angle of the elite players are greater than those of the collegiate players. The elbow angular velocity in the jump smash shows that the elite players are faster than the collegiate players. There are no significant differences between the two groups of players in other selected variables. Conclusions: As the results of this study show, the elite players are more powerful than the collegiate players. The faster shuttle velocity of the jump smash may result from the elbow angular velocity. We also find that when the players perform the jump smash, the elite players produce a larger flying downward angle than the collegiate players. Though they both reach the same height in the jump smash, the elite players show more effectiveness than the collegiate players.